Assessment of the Displacement Field Along a Surface Crack in a Flat Plate Using Optical Techniques. Issue 5 (7th September 2012) - Ribeiro, J.; Vaz, M.; Lopes, H.; de Melo, F.Q.; Monteiro, J.
<x xml:space="preserve">Abstract</x> Structural components may contain cracks, and for these components a crack tip represents a highly singular stress. The evaluation of the associated strain gradient is difficult to achieve with experimental discrete methods. An efficient alternative are the optical techniques which are non‐contact, and so delivering continuous information of the displacement fields and associated derivatives for strain evaluation. This paper describes some experimental methods to fully characterize the displacement field near a crack tip existing in flat plates. Three optical field techniques based on image analysis were used in the present work; respectively, Electronic Speckle Pattern Interferometry, Moiré Interferometry, and Digital Image Correlation. These methods allow different resolutions which can be adjusted according to the expected strain gradient. While the first method depends on the laser wavelength and position of the illumination sources, the second depends on the grating pitch and the last on the surface texture or painted speckle. Algorithms to derivate and filtering the displacement field are developed to compute the strain field and will be used for further works.